Transformation in Political Thought of Ayatollah Montazeri - Zaidi, Syed Zeeshan Haider (Technium Social Sciences Journal, 2022)
Among Shi'a scholars, the great jurists Akhund Khorasani and Mirza Na’ini tried to solve two crucial problems: the role of a secular constitution in an Islamic society, and the role of people in the government. But they failed to find a reasonable solution and these problems remained unsolved till the Islamic Revolution of 1979 and resurfaced before the writers of the new constitution in 1979. The solution Imam Khomeini offered was Velayat-i faqih in political issues which was made a basis and principle of the Iranian constitution after the revolution. Ayatollah Montaziri, who was the most competent and reliable student of Ayatollah Khomeini, played a key role in approving Valayet-i Faqih in the assembly. After some years, he was chosen as the next Veliyy-i faqih by the Mejlis-i Khobregan (assembly of religious experts). However, the relationship between him and his teacher became worse and a few months before his teacher's death, he resigned from his post. One of the reasons for his resignation was the newborn judicial system of Islamic republic of Iran. When the brother of his son in law was executed without proper investigation of his case along with execution of thousands of opposition activists without any court trial and evidence, he started to rethink about Vilayat-i faqih and its domain. This rethinking caused a transformation in his views about Valayet-faqih, he proposed a new version of velayet-faqih in which the rights of valiyy-i faqih are limited by assembly. I aim to explain, analyze, and compare his views about valayet-i Faqih before and after the death of Ayatollah Khomeini in this paper which contains two parts: The first part discusses his academic and political life, and the second part thoroughly analyses his political thought. In the new model of Velayat-i faqih, He rejected the concentrated power in the hand of Veliyy-i faqih and proposed a decentralized form of velayet-faqih which is limited by constitution.